Tourism Preferences Towards Blendung Beach and Nyamplungsari Beach in Pemalang Regency - Cahayani, Sevilla Inta (Universitas Negeri Semarang, 2019)
This study aims to determine and analyze how are tourists' preferences towards Blendung Beach and Nyamplungsari Beach attractions in Pemalang Regency by analyzing the characteristics of tourists and the factors that influence tourist interest in Blendung Beach tourism attractions and Nyamplungsari Beach so that the number of tourist visits can increase and be able to compete with other tourist objects. The research method used is quantitative research method with a sample of 100 respondents and using the preference values used are very good (4.6-5.0), good (3.6-4.5), good enough (2.6-3 , 5), less good (1.6-2.5) and not good (1.0-1.5). The results showed that tourist preferences towards both tourism objects Blendung Beach and Nyamplungsari Beach were in accordance classified as good enough, but also there were still indicators in the unfavorable and bad categories. Therefore there is a need efforts to improve tourist ratings and preferences so that it is expected to be able to encourage the increase in the number of tourist visits. Penelitian ini bertujuan untuk mengetahui dan menganalisis bagaimana preferensi wisatawan terhadap objek wisata Pantai Blendung dan Pantai Nyamplungsari di Kabupaten Pemalang dengan menganalisis karakteristik wisatawan dan faktor-faktor yang mempengaruhi minat wisatawan di objek wisata Pantai Blendung dan Pantai Nyamplungsari sehingga jumlah kunjungan wisatawan dapat meningkat dan dapat bersaing dengan objek wisata lainnya. Metode penelitian yang digunakan adalah metode penelitian kuantitatif dengan sampel 100 responden dan menggunakan nilai preferensi yang digunakan sangat baik (4,6-5,0), baik (3,6-4,5), cukup baik (2,6-3, 5), kurang baik (1,6 -2.5) dan tidak bagus (1.0-1.5). Hasil penelitian menunjukkan bahwa preferensi wisatawan terhadap kedua obyek wisata Pantai Blendung dan Pantai Nyamplungsari itu sesuai diklasifikasikan cukup baik, tetapi juga masih ada indikator dalam kategori tidak menguntungkan dan buruk. Oleh karena itu diperlukan upaya untuk meningkatkan peringkat dan preferensi wisatawan sehingga diharapkan dapat mendorong peningkatan jumlah kunjungan wisatawan.